Cytogenetic Aspects of Childhood Leukemias - Lampert, F.; Harbott, J.; Borkhardt, A. (Klinische Pädiatrie, 2013)
Recurrent non-random chromosome abnormalities, including numerical or structural changes such as translocations, inversions, insertions or deletions within the leukemia cell nucleus, have been discovered in approximately 80% of patients with a malignant hematological disease. These reciprocal translocations correlate with specific cellular subtypes of hematopoeisis at the stage of their maturation arrest and are therefore important for diagnosis. Some of these aberrations are independent prognostic indicators and help to stratify patients into different risk-adapted therapy groups. Owing to new laboratory methods such as the fluorescence in situ hybridization (FISH) and modified polymerase chain reaction (RT-PCR) the chromosomal breakpoints can be investigated and the rearrangements of genes which produce the abnormal proteins can be identified. Due to the high sensitivity of these available data a new prognostic factor, the “minimal residual disease” (MRD), can be investigated at diagnosis and at intervals during the treatment period. Since we now know which onkoproteins are involved, a target-directed therapy with inhibitors might be possible in the future.Standard cytogenetic and molecular genetic analysis of the leukemia karyotype is of the utmost importance for classification (WHO), therapy and therapy results in the acute childhood leukemias.
Keywords: cytogenetic analysis; chromosome abnormalities; childhood leukemias; hyperdiploidy; translocations